Analisa Forecasting Pada Penjualan Pakaian Di PT X - Andreas William; Silvia Rostianingsih; Yulia Yulia (Jurnal Infra, 2021)
PT X is garment company based in Surabaya that distributing clothing goods to Department Stores throughout Indonesia. PT X have an accumulation of goods in every Department Stores that are related as their business partners. This has an impact on the company's losses because high production costs do not match the remaining stock of goods in each store. Therefore, PT X needs an application that can forecast the number of categories of goods that will be sold in the future. Analysis of sales forecasting methods at PT X uses four different forecasting approaches, consists of Single Moving Average (SMA), Weighted Moving Average (WMA), Brown's Double Exponential Smoothing, and Holt’s Double Exponential Smoothing. The results of sales forecasting analysis on 4 categories of goods in the form of long blouses, short blouses, dresses, and robes from one of the stores, namely MDS Delta Plaza, show that the most appropriate method for PT X is Holt’s Double Exponential Smoothing (HES). The Mean Absolute Deviation (MAD) error value and the Mean Squared Error (MSE) of each category have the least value of the other methods.